Proceedings of the 28th International Conference on Software Engineering 2006
DOI: 10.1145/1134285.1134352
|View full text |Cite
|
Sign up to set email alerts
|

A case study of a corporate open source development model

Abstract: Open source practices and tools have proven to be highly effective for overcoming the many problems of geographically distributed software development. We know relatively little, however, about the range of settings in which they work. In particular, can corporations use the open source development model effectively for software projects inside the corporate domain? Or are these tools and practices incompatible with development environments, management practices, and market-driven schedule and feature decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(93 citation statements)
references
References 14 publications
(14 reference statements)
2
90
0
Order By: Relevance
“…Offshore teams have other options as well, for example adopting a matrix form rather than mirroring the structure of the client team [52]. Under appropriate circumstances, such as when a number of different product groups want to enhance and maintain a common resource, an open source style of organizing development, in which various users of a resource develop the functionality they need, can be effective [31].…”
Section: Research Summarymentioning
confidence: 99%
“…Offshore teams have other options as well, for example adopting a matrix form rather than mirroring the structure of the client team [52]. Under appropriate circumstances, such as when a number of different product groups want to enhance and maintain a common resource, an open source style of organizing development, in which various users of a resource develop the functionality they need, can be effective [31].…”
Section: Research Summarymentioning
confidence: 99%
“…Different organizations have used different terms: at Philips Healthcare, it is called ''Inner Source'' or ''Inner Source Software'' [4], while at Alcatel-Lucent it is called ''Corporate Open Source'' [5]. At Hewlett-Packard Corp. this phenomenon is referred…”
Section: Terminologymentioning
confidence: 99%
“…Gurbani et al have reported on a project-based Inner Source model applied at Alcatel-Lucent [5,24], where the shared asset was a telecommunications signaling server used in a Software Product Line (SPL) [26]. Wesselius reports on a projectbased Inner Source model as applied at Philips Healthcare and discusses business model aspects [4].…”
Section: Project-based Inner Source Modelmentioning
confidence: 99%
See 2 more Smart Citations